2010
DOI: 10.1016/j.csr.2009.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Estimating turbidity and total suspended matter in the Adour River plume (South Bay of Biscay) using MODIS 250-m imagery

Abstract: The Basque coastal waters (South Bay of Biscay) are directly influenced by the Adour River freshwater plume. The Adour outflow leads to important variations of suspended matter concentrations and turbidity, which in turn may affect biological productivity and water quality. This study aims at both developing specific algorithms and testing the efficiency of atmospherically corrected MODIS-Aqua 250-m surface reflectance product (MYD09) to map total suspended matter concentrations and turbidity within the Adour … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
140
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(148 citation statements)
references
References 29 publications
5
140
0
3
Order By: Relevance
“…Several models were reported with in-situ optical and CSPM values, and they were successfully applied to satellite images for CSPM retrieval [14,45,46]. The models developed in this study should be reliable considering the following two reasons: (i) the Rrs derived from in-situ measurements are less affected by atmospheric interference and are frequently used for spaceborne …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several models were reported with in-situ optical and CSPM values, and they were successfully applied to satellite images for CSPM retrieval [14,45,46]. The models developed in this study should be reliable considering the following two reasons: (i) the Rrs derived from in-situ measurements are less affected by atmospheric interference and are frequently used for spaceborne …”
Section: Discussionmentioning
confidence: 99%
“…Several models were reported with in-situ optical and C SPM values, and they were successfully applied to satellite images for C SPM retrieval [14,45,46]. The models developed in this study should be reliable considering the following two reasons: (i) the R rs derived from in-situ measurements are less affected by atmospheric interference and are frequently used for spaceborne sensor calibration and validation [5,47], and the NASA protocol [38] was strictly followed to ensure high quality optical measurements; and (ii) the synchronous in-situ C SPM values and R rs are more consistent in spatial and temporal scale, while the spatiotemporal scale gap problem always exists between satellite and in-situ observations [3].…”
Section: Discussionmentioning
confidence: 99%
“…Field surveys were performed in Cam Ranh Bay and Thuy Trieu Lagoon on [16][17][18][19] September during the rainy season in 2015 and on 12-13 February during the dry season in 2016. The latter was performed concomitantly with a Landsat 8 OLI image obtained at 10:00 a.m. on 14 February 2016 to minimize the difference between in situ measurements and remotely sensing data.…”
Section: Field Surveymentioning
confidence: 99%
“…Numerous studies on ocean color remote sensing for water quality parameter retrieval have been done, most of which follow three main methods: (i) using semi-analytic models based on the correlation between the inherent optical properties (IOPs) and the water quality parameters [7,[11][12][13][14][15]; (ii) using empirical models between IOPs and these parameters [1,16,17]; and (iii) using empirical models between remote sensing reflectance and the same parameters [18][19][20][21]. The third approach has been applied in this study, which is based on the correlation between remote sensing reflectance values extracted from Landsat 8 OLI and field measurements.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Miller and McKee [16] demonstrated that TSM concentration could be mapped successfully for a variety of coastal waters using MODIS 250 m band 1 data using a simple atmospheric correction model. Numerous other investigators (e.g., [17][18][19][20][21]) provide additional evidence that MODIS 250 m data can be used to examine water quality parameters related to TSM concentration using various atmospheric correction methods, image processing techniques and collection of field data.…”
Section: Introductionmentioning
confidence: 99%